The Hashtag Hustle: Law and Policy Perspectives on Working in the Influencer Economy (Edward Elgar Publishing, 2025)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This timely book sheds light on the cultural, economic and legal aspects of content creation as a form of labour, investigating concerns over working conditions, worker protection, and the status of the working relationship. Chapters written by leading experts in the field explore two opposing, yet complementary sides of work: labour as an invisible and underappreciated effort made by influencers, and labour as an economic enterprise.